Tailoring Multifunctional Small Molecular Photosensitizers to In Vivo Self‐Assemble with Albumin to Boost Tumor‐Preferential Accumulation, NIR Imaging, and Photodynamic/Photothermal/Immunotherapy. Issue 27 (2nd June 2022) - Luo, Shenglin; Luo, Xi; Wang, Xiaojiao; Li, Lian; Liu, Huiguo; Mo, Banghui; Gan, Hongbo; Sun, Wei; Wang, Liting; Liang, Houjie; Yu, Songtao
Abstract: Cancer immunotherapy has great potential in tumor eradication and metastasis suppression. However, systemic administration of immune adjuvants and inadequate specificity in cancer treatment, lead to restricted therapeutic benefits and potential immune‐related side effects in clinical settings. In this report, the synthesis of various lengths of heptamethine cyanine small molecules to act as multifunctional photosensitizers (PS) for tumor‐specific accumulation, near‐infrared (NIR) fluorescent imaging, and photodynamic/photothermal/immunotherapy is optimized. In particular, it is demonstrated that C8, which contains eight carbons on two N ‐alkyl side chains, efficiently self‐assembles with albumin to form nanosized dye‐albumin complexes. This feature facilitates C8 in vivo self‐assembly to remarkably improve its water‐solubility, NIR fluorescent emission, long‐term blood circulation, as well as tumor‐specific accumulation. More importantly, C8 not only exhibits a superior phototherapeutic effect on primary tumors, but also elicits secretion of damage associated molecular patterns, cytokine secretion, dendritic cell maturation, and cytotoxic T lymphocytes activation, ultimately triggering a sufficient antitumor immune response to suppress growths of distant and metastatic tumors. Hence, this multifunctional small molecular PS is characterized with excellent tumor‐preferential accumulation, imaging‐guided laser irradiation, and phototherapy‐induced in situ antitumor immune response, providing a prospective future of its use in tumor‐targeting immunotherapy. Abstract : A multifunctional small molecular photosensitizer (C8) in vivo self‐assembles with albumin to boost cancer targeting and photodynamic therapy/photothermal therapy/immunotherapy. C8 self‐assembles with albumin to form nanosized dye‐albumin complexes, exhibits tumor‐specific accumulation and profound phototherapeutic effect. C8‐mediated phototherapy elicits robust tumor immunogenic cell death, dendritic cell maturation, and cytotoxic T lymphocytes activation that effectively suppresses both primary and distant metastatic tumors.